Collaborative Governance in Environmental Impact Analysis of Margamulya Village Road Construction, Pasirjambu District, Bandung Regency - Edi Iskandar; Yogi Sahrul Danda; Shailla Khuzaimah Azhar; Iin Endah Setyawati; Dina (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The Environmental Impact Assessment (EIA) serves as a policy instrument to manage and mitigate environmental impacts arising from development activities. Beyond its technical dimension, the EIA process requires interaction and cooperation among multiple stakeholders within a collaborative governance framework. This study aims to examine the roles of government, private sector, and community actors in the implementation of collaborative governance in the EIA process in Margamulya Village, Pasirjambu District, Bandung Regency. This research adopts a qualitative approach using a case study design. Data were collected through in-depth interviews with relevant stakeholders, field observations, and document review. The findings reveal that the government performs regulatory, supervisory, and facilitative roles in the EIA process, while the private sector is responsible for fulfilling environmental obligations in accordance with applicable regulations. Meanwhile, the community plays a strategic role as directly affected stakeholders and as a channel for public aspirations and social control. However, collaborative practices among actors have not been fully optimized due to limited access to information, low community participation capacity, and weak coordination among stakeholders. This study highlights the need to strengthen collaborative governance mechanisms to improve the quality of the EIA process and to support sustainable development.